Analyzing consumer socialization of child - SHIN, Jihoon (KDI School, 2016)
Children’s socialization as consumers is influenced by various factors. This study examines the previous theories and models associated with a consumer socialization of child. The purpose of this study is to explore how the major factors (e.g., family, peer group, media, etc.) affect to children and how the effect of the major factor differs in accordance with the conditions. This study conducts surveys and applies statistical analysis, such as regression, ANOVA, t-test and chi-square to investigate the data. Result of the study provides meaningful implication to consumer socialization of child and offers managerial suggestion for marketing and sales targeting to children.
Thesis(Master) --KDI School:Master of Development Policy,2016